Dietary supplementation with Bacillus subtilis PB6 alleviates diarrhea and improves growth performance and immune function in weaned piglets fed a high-protein diet - Liu, Yang; Cao, Lei; Yu, Chenhao; Zhou, Qiang; Li, Hua; Zhang, Ruinan; Tang, Jiayong; Zhang, Zhiming; Luo, Zheng; Jiang, Xuemei; Fang, Zhengfeng; Lin, Yan; et al. (Frontiers in Veterinary Science, 2025)
This study aimed to evaluate the effects of dietary supplementation with Bacillus subtilis PB6 on growth performance, diarrhea scores, nutrient digestibility, immune function, and gut microbiota in weaned piglets fed a high-protein diet. A total of 96 weaned piglets were randomly divided into three groups in a randomized complete block design and received a low-protein diet (LP, 18.27% crude protein), a high-protein diet (HP, 20.97% crude protein), or a high-protein diet supplemented with probiotics (HPPRO, B. subtilis PB6 spores 2 × 1011 CFU/ kg) for 21 days. Each group had eight replicates with four piglets per replicate. The results showed that piglets fed the HPPRO diet had significantly higher average daily gain and average daily feed intake during days 8–14, days 15–21, and throughout the experimental period than piglets fed the LP diet (p < 0.01). In parallel, piglets fed the HPPRO diet had lower feed-to-gain ratio (F:G) values during days 8–14 than piglets fed the LP diet (p < 0.05). Piglets fed the HP diet had increased diarrhea scores than piglets fed the LP diet (p < 0.01), but the diarrhea scores of piglets fed the HPPRO diet were lower than those of the HP piglets (p < 0.01), which had the lowest nutrient digestibility. Moreover, piglets fed the HPPRO diet had lower plasma concentrations of haptoglobin than HP piglets (p < 0.05) and lower pig major acute-phase protein levels than HP and LP piglets (p < 0.05). The downregulation of genes (toll-like receptor-4, tumor necrosis factor-α [TNF-α], and TNF receptor-associated factor-6) in the ileal tissue associated with inflammation was observed in HPPRO-fed piglets compared to LP- and HP-fed piglets (p < 0.05). Piglets fed the HPPRO diet had increased relative abundance of genera related to proteolysis, such as g_Fusobacterium and g_Acidaminococcus, and genera related to butyrate production, such as g_Anaerostipes and g_Megasphaera. Furthermore, piglets fed the HPPRO diet had a higher concentration of butyrate in the colonic digesta than piglets fed the LP diet (p < 0.05). In conclusion, piglets fed the high-protein diet supplemented with 300-mg/kg B. subtilis PB6 had better growth performance, which was associated with relatively higher nutrient digestibility, an improved intestinal bacterial profile, and a lower inflammatory response.